The impact of reward systems for lecturers, communication culture, intrinsic motivation, and transformational leadership on institutional eﬀectiveness in Islamic higher education - Handoko, Handoko; Mesiono, Mesiono; Ananda, Rusydi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to analyze the influence of reward systems, communication culture, and intrinsic motivation on the institutional effectiveness of Islamic higher education institutions in Binjai City, emphasizing the mediating role of transformational leadership. The research is motivated by the importance of professional and high-quality educational management in addressing globalization challenges and meeting societal demands for higher education. Data were collected from 83 respondents, comprising lecturers at Institut Syekh Abdul Halim Hasan Binjai and Sekolah Tinggi Ilmu Tarbiyah Al-Washliyah, using a closed questionnaire. The analysis was conducted through simple correlation, multiple correlation, and path model testing.The findings reveal that reward systems, communication culture, and intrinsic motivation positively and significantly influence transformational leadership, contributing 2.9%, 2.3%, and 1.8%, respectively. Intrinsic motivation also directly impacts institutional effectiveness by 7%. However, other factors, such as organizational context and work culture, also play significant roles in determining overall institutional effectiveness. The practical implications of this study suggest the need for policies that support strengthening reward systems, fostering effective communication culture, and enhancing lecturers' intrinsic motivation to improve the institutional effectiveness of Islamic higher education. These findings provide insights for the management of Islamic higher education institutions in designing more effective institutional strategies.